Dry forming of aluminum alloys – Wear mechanisms and influencing factors. Issue 8 (August 2015) - Groche, P.; Resch, F.
<x xml:space="preserve">Abstract</x> Tribological contacts in sheet metal forming are accompanied by several wear phenomena. One of which is the transfer of material from the softer sheet material to the harder tool surface, namely adhesive wear. Forming of aluminum alloys makes high demands on forming processes. Aluminum alloys show a strong tendency of adhesion on common tool materials. Adhesions on tools reduce the surface quality, the dimensional accuracy of the parts and the process stability. In order to avoid adhesive wear during forming, nowadays a high amount of lubricant is applied to the aluminum sheets. Though economically and ecologically attractive, dry forming processes with aluminum sheets seem not to be possible. In order to develop advantageous tribological systems a comprehensive understanding of the acting mechanisms is necessary. This paper discusses the influence of the alloy composition and the influence of oxide layers on the adhesive wear in aluminum forming.